Health, culture and society : conceptual legacies and contemporary applications /: conceptual legacies and contemporary applications. ([2017]) - Ettorre, Elizabeth, 1948-; Annandale, Ellen; Hildebrand, Vanessa M; Porroche-Escudero, Ana; Rothman, Barbara Katz
No abstract available